2007
DOI: 10.1007/s00210-007-0183-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel pharmacological approaches to the treatment of renal ischemia-reperfusion injury: a comprehensive review

Abstract: Renal ischemia-reperfusion (I-R) contributes to the development of ischemic acute renal failure (ARF). Multi-factorial processes are involved in the development and progression of renal I-R injury with the generation of reactive oxygen species, nitric oxide and peroxynitrite, and the decline of antioxidant protection playing major roles, leading to dysfunction, injury, and death of the cells of the kidney. Renal inflammation, involving cytokine/adhesion molecule cascades with recruitment, activation, and diape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
157
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(171 citation statements)
references
References 563 publications
2
157
0
6
Order By: Relevance
“…Previous experiments show that various exogenous antioxidant agents such as allopurinol, melatonin, tocopherol, leflunomide, and some flavonoids have the potential to reduce I/R induced-renal injury and help the improvement of kidney function. [10,[13][14][15]26] In this study, we used AA as an exogenous antioxidant. AA is one of the water-soluble vitamins and is well known as a strong antioxidant agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experiments show that various exogenous antioxidant agents such as allopurinol, melatonin, tocopherol, leflunomide, and some flavonoids have the potential to reduce I/R induced-renal injury and help the improvement of kidney function. [10,[13][14][15]26] In this study, we used AA as an exogenous antioxidant. AA is one of the water-soluble vitamins and is well known as a strong antioxidant agent.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Experimentally, various agents such as novel antioxidants, antioxidant enzymes mimetics, flavonoids, nitric oxide synthase inhibitors, erythropoietin, peroxisome-proliferator-activated receptor agonists, erythropoietin, statins, adenosine, and calcium channel blockers were used to prevent kidney from I/R injury. [10] Many studies have shown that these antioxidants act as renoprotective against I/R induced cell damage. It has been demonstrated in dogs that pretreatment with allopurinol improves post-transplantation renal function and graft survival.…”
Section: Introductionmentioning
confidence: 99%
“…Although many have been evaluated clinically with a view to reducing renal I/R injury and improving renal function, none has been able to reduce mortality signifi cantly. I/R induced organ damage is multifactorial and interdependent, involving hypoxia, infl ammatory responses and free radical damage (Weight et al, 1996;Chatterjee, 2007;Boros and Bromberg, 2006). Thus, agents with antioxidant and antiinfl ammatory effects are thought to be useful in the clinical setting of I/R damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, in ischemia the depletion of energy stores and also the initiation of lipid peroxidation due to increased free radicals following reperfusion causes inhibition of membrane Na + ,K + -ATPase activity (Matsuzaki et al, 2007;Ş ehirli et al, 2008). Thus I/R-induced ARF, characterized by impaired renal function, reduced glomerular fi ltration and tubular sodium reabsorption have been related to the functional disorders of Na + ,K + -ATPase (Chatterjee, 2007). In agreement with these investigations, in our study there was a signifi cant decrease in the activity of Na + ,K + -ATPase in the saline treated I/R group, while BA treatment restored the enzyme activity possibly protecting the membrane structure by its antioxidant effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation